2021
DOI: 10.1097/md.0000000000026596
|View full text |Cite
|
Sign up to set email alerts
|

Severe bacterial infection in young infants with pyrexia admitted to the emergency department

Abstract: The objectives of this study were to understand the clinical presentations of febrile young infants with severe bacterial infection (SBI), and to investigate the pathogen variations throughout the vaccine era and after antenatal group B Streptococcus (GBS) screening. All infants < 90 days old with a body temperature of ≥38.0°C and admitted to the emergency department were retrospectively enrolled in our study. SBI was defined as a positive culture of urine, blood, or cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…Interestingly, we noted that an elevated neutrophil count was associated with a lower risk of bacterial co-infection. This was inconsistent with previous studies [1618] and could be explained by the distribution of neutrophil counts in hospitalised children infected with HAdV. Therefore, elevated ferritin levels in hospitalised children infected with HAdV was considered as high-risk of chlamydia co-infection, while elevated WBC level was regarded as high-risk of bacterial co-infection.…”
Section: Discussioncontrasting
confidence: 66%
“…Interestingly, we noted that an elevated neutrophil count was associated with a lower risk of bacterial co-infection. This was inconsistent with previous studies [1618] and could be explained by the distribution of neutrophil counts in hospitalised children infected with HAdV. Therefore, elevated ferritin levels in hospitalised children infected with HAdV was considered as high-risk of chlamydia co-infection, while elevated WBC level was regarded as high-risk of bacterial co-infection.…”
Section: Discussioncontrasting
confidence: 66%
“…This is consistent with previously reported studies. 10,18,19 We found that CRP and PCT as single biomarkers were strong predictors of SBIs and IBIs. In line with the findings of previous studies, 6,20,21 CRP ≥20mg/L performed best in predicting SBIs with an AUC of 0.741.…”
Section: Discussionmentioning
confidence: 79%